Quantifying health utilities of young adult orthodontic patients using the time trade-off method: a cross-sectional study - Budhaditya PAUL; Arun Srinivasa URALA; Shashidhar ACHARYA (Dental Press Journal of Orthodontics, 2023)
ABSTRACT Objective: To study the feasibility of time trade-off (TTO) method in quantifying health utility ratings in different types of malocclusion. Material and Methods: In this cross-sectional study, 70 orthodontic patients aged 18 years or above, reporting for treatment/consultation, were included and interviewed. Malocclusion-related health utilities were assessed through the TTO method, and oral health-related quality of life was measured with the help of Orthognathic Quality of Life Questionnaire (OQLQ). Angle’s classification of malocclusion was recorded. Bivariate analyses and multivariate Poisson’s regression were done to find out an association between the oral health utility values, OQLQ and demographic and clinical characteristics. Results: Patients with skeletal Class III malocclusion had lower health utility values than those with Class I and Class II malocclusions (p=0.013). Poisson’s regression showed that Angle’s Class II division 1 (0.90, CI 0.84 to 0.97), Class III (0.68, CI 0.59 to 0.95) and Skeletal malocclusion (0.79, CI 0.71 to 0.87) and OQLQ scores (1.0, CI 1 to 1.003) were found to be significant predictors of TTO utility scores. Conclusions: TTO utilities were found to be valid and well correlated with clinical findings. Health utilities could serve as useful and reliable markers of health-related quality of life (HRQL) among individuals or communities and help cost-effective preventive or intervention programs planning.